Pressurized Heavy Water Reactors : Atucha II - Riznic, Jovica R. (JSME series in thermal and nuclear power generation, 2022)
Pressurized Heavy Water Reactors: Atucha-II, the eighth volume in the JSME Series on Thermal and Nuclear Power Generation, provides a comprehensive and complete review of a single type of reactor in a very accessible and practical way. The book presents a close analysis of the Atucha reactor, covering reactor physics, aging management of major components, and the role of codes in PHWR and Nuclear Regulation and Licensing. Including contemporary capabilities and challenges of nuclear technology, the book offers solutions and advice on common problems faced, guiding the reader through safe and approved processes that will help them reach suitable solutions. Professionals involved in lifecycle assessments and researchers interested in the development and improvement of nuclear energy technologies will gain a deep understanding of PHWR nuclear reactor physics, design and licensing.